Studi kinetika fermentasi sari apel untuk pembentukan alkohol menggunakan metode bioteknologi - Aulia, Salwa Nadira (Maliki Interdisciplinary Journal, 2026)
The fermentation of apple juice using Saccharomyces cerevisiae yeast is one application of biotechnology that has the potential to produce alcohol, both for fermented beverages and as a raw material for bioethanol. The high simple sugar content in apple juice makes the success of fermentation highly dependent on substrate utilization dynamics and alcohol production rate. One of the main challenges in this process is the lack of understanding of fermentation dynamics and the influence of various parameters on optimal alcohol yield. The purpose of this article is to evaluate the fermentation dynamics of apple juice in alcohol formation and identify the main factors that affect the rate and efficiency of fermentation. The method used is a biotechnology approach by conducting studies and analyzing the fermentation dynamics of apple juice using Saccharomyces cerevisiae yeast, accompanied by observations of changes in sugar and alcohol levels throughout the fermentation process. The data on the dynamics were analyzed to understand the relationship between fermentation time, substrate utilization, and alcohol production. The results showed that fermentation temperature, inoculum amount, nutrient availability, and fermentation duration were important parameters that influenced the fermentation rate and alcohol content produced. Alcohol production increased as the sugar content decreased until it reached an optimal point, then tended to stabilize. In conclusion, studies on the dynamics of apple juice fermentation play a significant role in optimizing the fermentation process, thereby increasing alcohol production efficiency and supporting the development of biotechnology applications in the fields of food and renewable energy.